An endophytic fungus from Trichoderma harzianum SWUKD3.1610 that produces nigranoic acid and its analogues. Issue 14 (18th July 2019) - Han, MeiJun; Qin, Dan; Ye, TianTian; Yan, Xiao; Wang, JunQi; Duan, XiaoXiang; Dong, JinYan
Abstract: The objective of this study was to determine whether endophytic fungi, isolated from Kadsura angustifolia produce nigranoic acid and its highly oxygenated derivatives. From the 426 endophytic fungi screened, Trichoderma harzianum SWUKD3.1610 was detected to have a component with the same TLC R f value and HPLC retention time as authentic nigranoic acid. This component was further confirmed as nigranoic acid by investigating the chemical composition of the fungal extracts. Besides (1 ), one new triterpenoid, 7 β - schinalactone C (2 ), and two known minor compounds were isolated and characterized by HRESIMS, 1D and 2D NMR spectroscopic methods. Our study indicates that endophytic fungus may play an important role in increasing the quality of the crude drugs from Chinese medicinal plant K. angustifolia . This study is the first to isolate, characterize, and identify schitriterpenes-producing Trichoderma spp . Abstract :